2015
DOI: 10.1021/acs.langmuir.5b01681
|View full text |Cite
|
Sign up to set email alerts
|

UV-Induced Micropatterning of Complex Functional Surfaces by Photopolymerization Controlled by Alkoxyamines

Abstract: We report on the use of an alkoxyamine (AA) for fabrication of functional micropatterns with complex structures by UV mask lithography. The living character of the polymer surface and the vertical spatial control of the repolymerization reaction from few tens of nanometers to few micrometers were demonstrated. The impact of the main parameters governing the controlled polymerization and the reinitiation process activated by light or heat was investigated. Micropatterning is shown to be a powerful method to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…The photoinduced NMP process was also proposed and developed for fabrication functional micropatterns with complex structures such as hydrophilic/hydrophobic or luminescent surfaces simply by using a mask ( Figure 42). [368] The self-healing process was reported in covalent polymer networks via the photodissociation of alkoxyamine junctions. [369] Insert Figure 42.…”
Section: Photomediated Nmpmentioning
confidence: 99%
“…The photoinduced NMP process was also proposed and developed for fabrication functional micropatterns with complex structures such as hydrophilic/hydrophobic or luminescent surfaces simply by using a mask ( Figure 42). [368] The self-healing process was reported in covalent polymer networks via the photodissociation of alkoxyamine junctions. [369] Insert Figure 42.…”
Section: Photomediated Nmpmentioning
confidence: 99%
“…[91] In the past 20 years, efforts have been made to develop light-mediated NMP: [92][93][94][95][96] in 2014, Telitel et al performed light-mediated NMP on a cross-linked polymer matrix surface and fabricated cross-linked micropatterns with trifunctional monomer, trimethylolpropane triacrylate (TMPTA). [97,98] More recently, Guselnikova et al reported a plasmon-induced NMP on gold surface to grow block copolymer brushes. [99] Both contributions suggested light-mediated SI-NMP to be a promising technique to fabricate patterned polymer brushes.…”
Section: Surface-initiated Nitroxide-mediated Polymerization (Si-nmp)mentioning
confidence: 99%
“…Analyses of the chain length as well as the polydispersity of polymers can be thus performed. At present, only a low or moderate control of the polymer size is obtained by photopolymerization, high polydispersity indices being determined by size exclusion chromatography (SEC) [124,125]. This result is counterintuitive since, from a theoretical point of As often observed, the two-component systems Fe complex/Ph 2 I + (0.2%/2%, w/w) were less efficient than the three-component photoinitiating system Fe complex/Ph 2 I + /NVK (0.2%/2%/3%, w/w/w) for the FRP of TMPTA.…”
Section: Iron Complexesmentioning
confidence: 99%
“…At present, only a low or moderate control of the polymer size is obtained by photopolymerization, high polydispersity indices being determined by size exclusion chromatography (SEC) [124,125]. This result is counterintuitive since, from a theoretical point of view, a higher control of the polymerization process should be obtained by using light, when the polymerization reaction is carried out at room temperature.…”
Section: Iron Complexesmentioning
confidence: 99%
See 1 more Smart Citation